A Systematic Review on Oral Health Care Programs for the Elderly in Korea (2009∼2020) - Eun-Seo Choi; Im-Hee Jung; Do-Ah Kim; Eun-Som Lee; Hee-Jung Lim (치위생과학회지, 2021)
Background: Various oral health management programs in Korea affect the oral health improvement in the elderly Several studies have been conducted to date; however, those studies have not shown uniform results due to the differences in research methods or designs. Hence, this study aimed to review the overall research trends of the reported oral health care programs for the elderly in Korea, verify their effects, and clarify them based on the systematic literature review. Methods: The literature search selected intervention studies that applied the oral health care program for the elderly in Korea from 2001 to 2020. Following the COre, Standard, and Ideal (COSI) models presented by the US National Library of Medicine, we selected databases including Korean studies Information Service System (KISS), ScienceOn, Research Information Sharing Service (RISS), DBpia, PubMed, and Google Scholar. Of the 1,335 studies searched using keywords, titles, and abstracts, 21 were finally selected based on primary and secondary exclusion criteria. Results: The most frequent intervention period was 4 weeks, and the number of interventions varied between 2 and 90 times. As for the type of intervention, 14 studies that conducted both theory and practice were the most frequent. Significant differences in the clinical indicators, such as calculus, halitosis, salivation rate, swallowing function, and dry mouth, were found in most oral health care programs. Conclusion: Based on the results of this study, the intervention program needs further verification using multiple indicators in future studies. In addition, a study extending the intervention period and the number of samples is considered necessary for verifying continuous effectiveness of the intervention program.